Taxonomic changes for Neotropical pinhole borer ambrosia beetles (Coleoptera: Curculionidae: Platypodinae) - Kirkendall, Lawrence R. (Zootaxa, 2024)
Stephen L. Wood re-defined Platypus such that its members are native to realms outside of the Americas and transferred most Neotropical species out of that genus. I have come across 44 species that still remain, though, and these are treated here. In total, I report 49 new generic assignments, 30 of which are transfers out of Platypus. I propose 22 new synonymies, eight of which are Platypus species that are synonymized with previously transferred species. Six Neotropical species are left in Platypus, for reasons detailed in the text. These taxonomic acts affect the compositions of eight of the 11 Neotropical genera of core Platypodinae. The following species are transferred from Platypus Herbst, 1793: Cenocephalus dubiosus (Schedl, 1933) comb. nov., Cenocephalus neotruncatus (Schedl, 1972) comb. nov.; Costaroplatus barbosai (Schedl, 1972) comb. nov., Costaroplatus devius (Schedl, 1976) comb. nov., Costaroplatus mixtus (Schedl, 1976) comb. nov., Costaroplatus roppai (Schedl, 1978) comb. nov.; Epiplatypus bicaudatulus (Schedl, 1935) comb. nov., Epiplatypus carduus (Schedl, 1936) comb. nov., Epiplatypus complanus (Schedl, 1967) comb. nov., Epiplatypus grandiporus (Schedl, 1961) comb. nov., Epiplatypus insculptus (Schedl, 1967) comb. nov., Epiplatypus macroporus (Chapuis, 1865) comb. nov., Epiplatypus perforans (Schedl, 1961) comb. nov., Epiplatypus propinquus (Schedl, 1959) comb. nov., Epiplatypus quadrispinatus (Chapuis, 1865) comb. nov., Epiplatypus sallei (Chapuis, 1865) comb. nov., Epiplatypus sequius (Schedl, 1935) comb. nov.; Euplatypus detectus (Schedl, 1976) comb. nov., Euplatypus erraticus (Schedl, 1972) comb. nov., Euplatypus longulus (Chapuis, 1865) comb. nov., Euplatypus perplexus Bright, 1972 comb. nov., Euplatypus rugosifrons (Schedl, 1933) comb. nov., Euplatypus vexans (Schedl, 1972) comb. nov.; Megaplatypus asperatus (Schedl, 1976) comb. nov., Megaplatypus carinifer (Schedl, 1970), Megaplatypus durus (Schedl, 1936) comb. nov., Megaplatypus eversus (Wood, 1971) comb. nov., Megaplatypus gagates (Schedl, 1976) comb. nov., Megaplatypus irrepertus (Schedl, 1936) comb. nov., Megaplatypus lineaticornis (Schedl, 1936) comb. nov., Megaplatypus paramonovi (Schedl, 1972) comb. nov., Megaplatypus schedli (Wood, 1966) comb. nov., Megaplatypus vafer (Schedl, 1972) comb. nov.; Teloplatypus caligatus (Schedl, 1972) comb. nov. Costaroplatus bidens (Schedl, 1970) comb. nov. and Costaroplatus darlingtoni (Reichardt, 1965) comb. nov. are transferred from Megaplatypus Wood, 1993. Costaroplatus vonfaberi (Reichardt, 1962) comb. nov. is transferred from Platyphysus Wood, 1993. Epiplatypus striatus (Chapuis, 1865) comb. nov., Megaplatypus contextus (Schedl, 1963) comb. nov., Megaplatypus decorus (Schedl, 1936) comb. nov. and Megaplatypus dignatus (Schedl, 1936) comb. nov. are removed from Euplatypus Wood, 1993. Epiplatypus ornatus (Schedl, 1936) comb. nov. is transferred from Teloplatypus Wood, 1993. Euplatypus jamaicensis Bright, 1972 comb. nov., Megaplatypus discolor (Blandford, 1896) comb. nov., Teloplatypus brasiliensis (Nunberg, 1959) comb. nov., Teloplatypus nudus (Schedl, 1936) comb. nov. and Teloplatypus pernudus (Schedl, 1936) comb. nov. are transferred from Epiplatypus Wood, 1993. Costaroplatus ornatus (Schedl, 1936) comb. nov., is transferred from Cenocephalus Chapuis, 1865. Megaplatypus acutidens (Blandford, 1895) comb. nov. and Megaplatypus despectus (Schedl, 1971) comb. nov. are transferred from Tesserocerus Saunders, 1837. New synonymies are proposed as follows: Cenocephalus rugicollis Schedl, 1952 (= Cenocephalus epistomalis Wood, 1966 syn. nov.); Tesserocerus forcipatus Schedl, 1972 (= Platypus aplanatus Schedl, 1976 syn. nov.); Tesserocerus retusus Guérin-Méneville, 1838 (= Tesserocerus guerini ssp. montanus Schedl, 1960 syn. nov.); Tesserocerus simulatus Schedl, 1936 (= Platypus bilobus Schedl, 1961 syn. nov.); Tesserocerus spinax Blandford, 1896 (= Tesserocephalus forficula Schedl, 1936 syn. nov.); Costaroplatus carinulatus (Chapuis, 1865) (= Platypus umbrosus Schedl, 1936 syn. nov.); Costaroplatus shenefelti Nunberg (1963) (= Platypus abditulus Wood, 1966 syn. nov.); Costaroplatus vonfaberi (Reichardt, 1962) (= Platypus convexus Schedl, 1972 syn. nov.); Epiplatypus sallei (Chapuis, 1865) (= Platypus quadricaudatulus Schedl, 1934 syn. nov. and = Platypus filaris Wood, 1971 syn. nov.); Euplatypus longulus (Chapuis, 1865) (= Platypus dimidiatus Chapuis, 1865 syn. nov. = Platypus mulsanti Chapuis, 1865 syn. nov. and = Platypus pseudolongulus Schedl, 1963 syn. nov. ); Megaplatypus acutidens (Blandford, 1895) (= Tesserocerus alternantes Schedl, 1977 syn. nov.); Megaplatypus durus (Schedl, 1936) (= Platypus arcuatus Schedl, 1976 syn. nov.); Megaplatypus fuscus (Chapuis, 1865) (= Platypus marginatus Chapuis, 1865 syn. nov., = Platypus granarius Schedl, 1952 syn. nov., and = Platypus obsitus Schedl, 1976 syn. nov.); Megaplatypus irrepertus (Schedl, 1936) (= Platypus sulcipennis Schedl, 1976 syn. nov.); Neotrachyostus abbreviatus (Chapuis, 1865) (= Platypus concavus Chapuis, 1865 syn. nov.); Teloplatypus enixus (Schedl, 1936) (= Platypus interponens Schedl, 1978 syn. nov.); Teloplatypus ratzeburgi (Chapuis, 1865) (= Platypus pallidipennis Blandford, 1896 syn. nov.). Platypus simpliciformis Wood, 1966 had been transferred by Wood (1993) to both Megaplatypus and Euplatypus by mistake; I propose keeping it in Megaplatypus. Six Neotropical species are left in the genus Platypus with the status incertae sedis: Platypus armatus Chapuis, 1865; Platypus dorsalis Schedl, 1972; Playpus quadrilobus Blandford, 1895; Platypus squamifer Schedl, 1963; Platypus subaequalispinosus Schedl, 1936; and Platypus trispinosus Chapuis, 1965. These taxonomic changes prepare the foundations for future revisionary work on the American Platypodinae.